Factors influencing consumers’ behavioral intention to waste reduction in restaurant - Tan, Kat Ni (2022)
This research mainly is to focus on the factors influencing consumers’ behavioral intention to waste reduction in restaurant. This research provides an overview of the study and includes sections on the research overview, literature review, methodology, data analysis and discussion, conclusion, and implications. In addition, this paper mainly discuss the factors that will influence consumers’ behavioural intention to reduce waste in restaurant. In this research, a total 260 questionnaires been distributed and all the 260 questionnaires are collected. The data processing and analysis were done with SPSS version 23. The results showed that subjective norms, attitude, and perceived behavioral control proposed significant relationship with consumers’ behavioral intention. The managerial implications also listed in the research to provide insight for the consumers to understand what can be done to influence them to reduce waste when dining out in restaurant. The limitations of the study and the recommendations are provided for the researchers to conduct future research.